THE EFFECT OF INTERNET MEDIA USAGE TOWARD LEARNING INTEREST THROUGH LEARNING MOTIVATION AS A MODERATOR VARIABLE - Silviana, Devi; Musafik, Mohammad Naim; Sulistyanto, Irwan (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2023)
This research aims at analyzing the significant effect of: (1) the effect of internet media usage toward learning interest; (2) the effect of learning motivation toward learning interest; (3) the effect of internet media usage toward learning motivation and (4) the impact of internet media usage toward learning interest through learning motivation as a moderator variable. The method used is a quantitative approach, with questionnaire to measure the variable. The samples consist of 199 students who are taken by random sampling at the first grade of SMA Negeri 7 Kediri, it is calculated using Slovin Pattern formula. The path analysis used to analyze the data is (1) simple linear regression and (2) multiple linear regression. The result reveal that: (1) Internet media usage has positive significant effect toward learning interest about 26,3%; (2) Learning motivation has positive significant effect toward learning interest about 42,7%; (3) Internet media usage has positive significant effect toward learning motivation about 24,4% and (4) Internet media usage has an indirect impact toward learning interest through learning motivation as a moderator variable about 25,1%, while the direct impact is about 26,1%. It shows that the result of indirect impact is greater than direct impact. It is recommended that internet media usage is very well used as a new innovation in learning that is able to foster students’ learning interest, but it must be accompanied by learning motivation that encourages students to use the internet wisely and finally it has a better effect on improving students’ academic performance.